Pengaruh Edukasi Dengan Pendekatan Persepsi Kerentanan Dan Persepsi Manfaat Dalam Perubahan Perilaku Pasien Hipertensi Di Kecamatan Dusun Tengah: Pengaruh Edukasi Dengan Pendekatan Persepsi Kerentanan Dan Persepsi Manfaat Dalam Perubahan Perilaku Pasien Hipertensi Di Kecamatan Dusun Tengah - Dyan Fitri Nugraha; Saftia Aryzki; Novi Damayanti (LPPM Universitas Sari Mulia, 2023)
Background: Hypertension is the most common disease suffered by the people of Indonesia,because the level of adherence to taking medication is one of the behaviors that shows that the low rate of adherence can increase the recurrence rate of hypertension so that it can lead to complications. There are several approaches that can be given to improve adherence to taking antihypertensive drugs, which can be give an education with an approach to percepstion of vulnerability and perception of benefits through a video-based media. Objective: This study aims to determine the effect of education with a perception vulnerability and perception benefits in changing the behavior of hypertension patients in the Sub-district of Dusun Tengah. Methods: True experimental research with pretest and posttest control group design approach. Sampling was done by stratified random sampling. The research sample amounted to 88 patient. The data was obtained by using a questionnairewhich was distributed. There are two groups used, namely the control group and the intervention group. Results: The result of statistical analysis using ordinal regression test with a p-value 0,000 which a significant on the provision of education with a perception vulnerability and percepstion benefits approach in changing the behavior of hypertensive patient through a video media. Conclusion: There is an effect of providing education with a perception of vulnerability and percepstion of benefits through video media in changin the behavior of hypertension patients in the Sub-district of Dusun Tengah.